La Tradició codicològica i litúrgica de l'homiliari carolingi de Luculentius a Catalunya : la recensió catalana: inventari i homilies recuperades - Altés i Aguiló, Francesc Xavier (Miscel·lània litúrgica catalana, 2010)
The carolingian homiliary of Luculentius, written in the end of 9th century, possibly in Italy, had a wide diffusion in Catalonia contrasting with a rather reduced italian tradition. This work of an enigmatic Luculentius, designated in Catalonia with the tipoligical names of Collectaneum and Dispositus, is contained complete in only two homiliaries copied on 956/957 at the monastery of Sant Cugat del Vallès, near Barcelona. Its codicological tradition in Catalonia and its library and geographical range is attested through the Divine Office homiliaries and, particularly, through the newly identified ninety-five codex fragments, forty of them copied between 925/950 and the first quarter of 11th century, transmitting an own catalan recension or catalan family of the Luculentius. This is a recension to be taken into account for the critical edition of the Luculentius, from which we edit here the three first homilies, absent from Sant Cugat codexs.